Dampak Positif Negatif Pembelajaran Online Dalam Sistem Pendidikan Indonesia Pasca Pandemi Covid-19 - Roselina Febria Karmen; Farid Pribadi (ADALAH, 2022)
During the Covid-19 pandemic that hit Indonesia, it had an impact on various fields, including education. The learning process was initially carried out face-to-face but expertly online (online). This study aims to determine the positive and negative impact of online learning in the Indonesian education system after the COVID-19 pandemic. This type of research uses a qualitative literature study. The results showed that there were negative impacts, namely, lack of understanding of the material, lack of socialization, quickly spending internet quota, declining eye health, and difficulty in doing group assignments. And there are positive impacts, namely, having a lot of family time, getting help from the government in the form of free internet quotas, making students active and independent. It is concluded that the implementation of online learning has several negative and positive impacts.